Congenital Pulmonary Airway Malformation (CPAM) follow up from 23 week of gestation - Parveen, Nuzhat; Khatun, Tarannum (Med Phoenix, 2017)
The development of the respiratory system starts at 3 weeks of gestation, and aberrations in developmental processes may result in structural abnormalities collectively referred to as bronchopulmonary foregut malformations. These lesions include congenital cystic adenomatoid malformations (CCAMs), sequestrations and infantile lobar emphysema. Case presented is of right lung CCAM diagnosed at 23 weeks of gestation, followed during antenatal periods for complications, delivered at 39 weeks, planned thoracotomy with lobectomy done on 3rd day of life and followed up till 1 year. Detailed anomaly scan and close monitoring for structural abnormalities of fetus is needed for appropriate management. Relationship of CPAM with early pregnancy severe infections remains to be established. Med Phoenix Vol.2(1) July 2017, 63-66